Large debt financing: syndicated loans versus corporate bonds - Yener Altunbas; Alper Kara; David Marqués-Ibá\~nez (European Central Bank (ECB), 2009)
Following the introduction of the euro, the markets for large debt financing experienced a historical expansion. We investigate the financial factors behind the issuance of syndicated loans for an extensive sample of euro area non-financial corporations. For the first time we compare these factors to those of its major competitor: the corporate bond market. We find that large firms, with greater financial leverage, more (verifiable) profits and higher liquidation values tend to prefer syndicated loans. In contrast, firms with larger levels of short-term debt and those perceived by markets as having more growth opportunities favour financing through corporate bonds.
Keywords: D40; F30; G21; 330; corporate bonds; debt choice; syndicated loans; the euro; Kreditgeschäft; Unternehmensanleihe; Unternehmensfinanzierung; Eurozone